Тасмолинская культура Центрального Казахстана в исследованиях начала ХХІ века - Бейсенов, А.З. (Археологія і давня історія України, 2018)
Современный этап изучения тасмолинской культуры характеризуется получением новейших данных, в том числе и из ранее неизвестных видов памятников, также реализацией задач, направленных на проведение мультидисплинарных изысканий. В настоящем сообщении впервые на русском языке публикуется серия радиоуглеродных дат по погребальным памятникам и поселениям тасмолинской культуры, а также по погребениям коргантасского периода. Автор делает оговорку, что все данные, имеющиеся в настоящее время в корпусе источников по тасмоле, находятся в процессе исследований и какие-либо основные выводы будут впереди. According to archaeological researches, in the early Saka period the steppe areasof Central, Northern Kazakhstan and the Southern Trans-Urals were inhabited by the tribes of the great Tasmola historical and cultural community. The tribes of Central Kazakhstan constitute the core of this community. For the first time, Tasmola archaeological culture was discovered and described by M. K. Kadyrbaevin 1966. Today a significant amount of new data has been gathered, which allows us to expand our understanding of the peculiarities of that culture. The article presents an overview of the main content of new studies and publishes data on radiocarbon analyses, first obtained from the monuments of Tasmola culture. More than 60 analyses from the monuments of the Early Iron Age of Central Kazakhstan were made by A. Z. Beisenov in the Kiev radiocarbon laboratory (Kiev, Ukraine), in the laboratories of the Royal University of Belfast, (Northern Ireland, Great Britain), the Russian State Pedagogical University (Sankt-Peterburg, Russia). The article contains data from 41 analyses on Tasmola culture and 6 analyses on the monuments of the Korgantass period. In Tasmolaseries 33 dates were obtained from 31 burials, 8 dates were obtained from 6 settlements. At the present stage of the research the origins of Tasmola culture can be attributed to the middle of the 8th century BC. During the late V — early IV centuries BC there is a change of cultures, there are few burial places of the Korgantass periodin the region. The author believes that further studies are needed for more detailed internal periodization of Tasmola culture. Now we can say that numerous and most vivid monuments are common for the early stage of culture. All present researches are carried out in the eastern part of Central Kazakhstan.